EVALUTION OF OCCUPATIONAL HEALTH AND SAFETY SYSTEM ACCORDING TO ISO 45001 : 2018 Applied Research IN BAGHDAD COMPANY FOR SOFT DRINKS - خلف بتول عطية; حسن ماجد حميد (Journal of Economics and Administrative Sciences, 2019)
Represent a topic occupational safety and health management is one of the priorities of the loading organization in the business environment ,and one of the requirement for the success and its impact on the productivity of workers and their performance in an appropriate working environment .The international responses to the problems that accompany the technological and industrial development of the business environment are the issuance of ISO 45001:2018 aimed at providing an appropriate framework for controlling risks , reducing injuries and work accidents and improving work performance ,after realizing the environmental relationship between safe and sound work with competition .The search’s issue is represented with the existence of a gap between specification requirements ISO 45001 : 2018 and the practical reality in the company’s search sample. The interview was conducted with department managers and laboratories as well as access to records, and use checklist, in order to reach the desired results, also the use of a number of statistical analysis methods, the most important of which is the arithmetic mean, weights, percentages, and diagrams. The research result and analysis are explained that safety occupational and health management systems compared to requirements of ISO 45001:2018 in all major and sub-paragraphs the average correspondence reached (3.22), the percentage of the conformity range was (38%), and the gap size (62%), which is close to a partial and unannounced application of the implementation of the standard requirements.